PENGEMBANGAN LKPD BERBASIS INKUIRI TERBIMBING PADA MATA PELAJARAN IPAS DI KELAS V SDN LEMAH PUTRO 1 - Zebua, Armina; Wibowo, Satrio; Wahyu Andjariani, Endang (Universitas Islam 45 Bekasi, 2025)
This study was motivated by the teacher's efforts to make students play an active role in learning by choosing media that train skills and critical thinking, so that students actively understand the concept of IPAS. One of them is by using guided inquiry-based LKPD media. The purpose of this study was to help fifth grade learners at SDN Lemah Putro 1 with their understanding of the topic “How We Live and Grow” by creating guided inquiry-based worksheets and then measuring their reactions to the material. A four-aspect research and development model or Four-D model (Define, Design, Develop, and Disseminate) was used in this study. Questions and surveys, as well as tests for media and material experts were some of the research tools used. In evaluating the practicality of LKPD, researchers conducted validity tests with media expert lecturers and material expert teachers, to determine the practicality of LKPD, data were collected through questionnaires filled out by media experts and material experts, as well as student answers and test questions. With an average validity percentage of 90.5%, guided inquiry-based LKPDs meet the criteria of very feasible according to media experts and material experts. A poll of 89% was used by media experts to assess the LKPD and 92% by material experts. In the guided inquiry-based LKPD, 92% of students stated that the criteria were very interesting for their learning achievements, and students' responses to the guided inquiry-based LKPD were very interesting.